Pembinaan Akhlak Melalui Dharma Pramuka: Studi Fenomenologi di Madrasah Aliyah Negeri - Maryanis Maryanis (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2020)
This research aims to explain the material, methods and evaluation system in moral coaching through dharma Pramuka in MAN Pariaman City. Research uses qualitative methods with this type of phenomenological research. The results in this study show that the material in moral coaching through the Scout dharma in MAN Pariaman City is contained in the scout honor code that is takwa to the One True God; the love of nature and the compassion of fellow human beings are willing in helping anyone and patiently do for good. Methods in moral coaching through dharma Pramuka in MAN Pariaman City there are exemplary methods, habituation and lecture methods, and evaluation system in moral coaching through dharma scouting in MAN Pariaman City is carried out through muhasabah, devotion al-all activities with evening wirid events.